The spatial-temporal dimension of the alliances NATO & CSTO - Dincă, Marian; Josan, Nicolae (ROU, 2022)
Despite being structural entities which have relatively recently emerged, the alliances have caught global attention and interest, in a relatively short time, this giving a very well confined place in the approaches of the great political-military strategists, at all levels. The history and evolution of the North-Atlantic Alliance are closely connected to the security environment as well as to the geopolitical and geostrategic reality, specific to a particular moment. The emergence of an alliance has led to the formation of a counter alliance, meaning to bring a balance, even a fragile one on the surface.